Iranian and Saudi mutual (mis)representations: a study of the relationship between discourses of othering, political confrontation and sectarian strife - Mohammad, T (2018)
The objective of this dissertation is to study the concept of the ‘representation of the Other’ in the context of Saudi-Iranian confrontation and Shi’i-Wahhabi strife. The aim of this study is to incorporate discourse analysis, to study mutual Iranian-Saudi representation of each other in political, religious and media genres. Therefore, taking on a relatively new approach to the study of these two states. By conducting a diachronic approach from 1979 to 2009, this dissertation discusses the employment of tropes and narratives to explore the concept of the ‘representation of the Other’ in the context of Saudi-Iranian confrontation. Since the constructivist approach allows for a better understanding to the representation of Othering in socio-historical and International Relations settings, Foucault’s power-knowledge relations; Edward Said’s concept of Othering and dichotomies in his Orientalism thesis; and image theory based on Hermann and Fischerkeller’s image of the enemy are employed. Finally, by investigating three main Iranian and Saudi spheres/discourses, namely the political (speeches of the elite), religious (Friday prayer sermons) and media (newspaper editorials) discourses, this study will try to explain how Othering is understood and functions in the Iranian-Saudi discourse, its relationship to political rivalry and religious conflict and how they are understood as cases of political propaganda or religious polemics. The study findings identify a paradigm shift in analysis of the Saudi-Iranian relationship, moving away from conventional geopolitical and sectarian paradigms, which have been dominant. I conclude that religious and sectarian identities remained a propaganda tool, whereas, the nature of the agenda promoted by both sides was political in nature. The Othering framework employed marks a shift in the longstanding understanding of ‘rivalry’ in the SaudiIranian setting, where the relations between these two sides were dependent on the perceptions of each other, rather than embodying any innate or deeply grounded ideological fervour